EFECTIVITY OF CONTEXTUAL LEARNING TOWARDS MATHEMATICAL COMMUNICATION SKILLS OF THE 7TH GRADE OF SMPN 2 KOLAKA - Ahmad Rustam; Andi Lilis Handayani (JME (Journal of Mathematics Education), 2017)
This study was a quasi experimental research with the aim to know the effectiveness of contextual learning in kolaka city to the skills of mathematical communication. Population in this research was all student of class VII SMP Negeri 2 Kolaka Academic Year 2015/2016. To avoid a large bias in the determination of research samples, the researchers conducted several stages i.e. firstly to test homogeneity against the groups that had formed in the population. After that, took two classes of control and experiment group. Â Data collection techniques applied tests and observations. Data analysis techniques used descriptive statistics using data centering and data dissemination, then inferential statistics using Independent t-test. The results of descriptive research indicated that the mathematical communication skills of the students taught by using contextual learning of kolaka city consisting of 24 students showed the average value of 71.18 while students who were taught with conventional learning consisting of 27 students showed the mean value of 60.34. Furthermore, the results of inferential statistical analysis of hypothesis testing by using t-test obtained tcount as much as (2.03658) ttabel (1.67655), indicating that H0 was rejected and H1 was accepted, meant that there was a significant difference between the mathematical communication skills of the students who are taught with contextual learning of kolaka city and conventional learning on the 7th grade students of SMP Negeri 2 Kolaka. From the result of this research, it can be concluded that the mathematical communication skills of the students who are taught by contextual learning of kolaka city is more effective than mathematical communication skills of the students taught by conventional learning in class VII SMP Negeri 2 Kolaka.